Free Field Approach to Solutions of the Quantum Knizhnik-Zamolodchikov Equations - Kuroki, K.; Nakayashiki, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2008)
Solutions of the qKZ equation associated with the quantum affine algebra Uq(^sl2) and its two dimensional evaluation representation are studied. The integral formulae derived from the free field realization of intertwining operators of q-Wakimoto modules are shown to coincide with those of Tarasov and Varchenko.